Determinant Factors of Educational Insurance Demand among Parents in North Padang Lawas Regency - Ismu Hadi Siregar; Nurul Jannah; Muhammad Ikhsan Harahap (Fakultas Syariah IAIN Langsa, 2026)
This study aims to analyze the effects of parents’ income, consumer behavior, long-term planning preferences, perceived benefits of education insurance, and social environment on the demand for education insurance. The research adopts a quantitative approach using a survey method involving 100 respondents who are parents of school-aged children. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with the assistance of SPSS. The partial test (t-test) results indicate that all independent variables have a positive and significant effect on the demand for education insurance. Parents’ income shows a t-value of 9.792 with a regression coefficient of 0.329 and a significance level of 0.000. Consumer behavior has a significant effect with a t-value of 4.737, a coefficient of 0.199, and a significance level of 0.000. Long-term planning preferences also demonstrate a significant effect with a t-value of 4.253, a coefficient of 0.329, and a significance level of 0.000. The perceived benefits of education insurance emerge as the most dominant variable, with a standardized beta coefficient of 0.675, a t-value of 6.422, and a significance level of 0.000. Meanwhile, the social environment has a significant effect with a t-value of 2.965, a coefficient of 0.033, and a significance level of 0.000. Simultaneously, the F-test results show an F-value of 24.614, which is greater than the F-table value of 2.31, with a significance level of 0.000, indicating that all independent variables jointly have a significant effect on the demand for education insurance. These findings suggest that the demand for education insurance is influenced by a combination of economic factors, consumer behavior, perceived benefits, long-term planning orientation, and social environment. Therefore, improving financial literacy and conducting comprehensive dissemination of the benefits of education insurance are essential to enhance public demand for education insurance.